AVAILABILITY, ACCESSIBILITY AND USE OF ICTS BY NIGERIAN WOMEN ACADEMICS - Olatokun, Wole Michael (Malaysian Journal of Library and Information Science, 2017)
This study investigated the availability, accessibility and use of Information and Communication Technologies (ICTs) among women academics in six universities in South Western Nigeria. The study adopted a survey design approach and the questionnaire was administered on 246 women academics in the six universities. Findings revealed that the use of ICT facilities such as computers, printers, Internet, individual websites, photocopiers, telephones and mobile phones was relatively high among the respondents compared to the use of scanners, facsimiles, videoconferencing, and teleconferencing. Also, the women academics used the ICT facilities for various tasks notably for statistical analyses, word processing, Internet browsing and searching for information, electronic communications and preparation of course materials. Analyses also confirmed notable differences in women academics access to the ICT facilities compared with their male counterparts and some factors responsible for this were identified. The study argues that though increasing availability and access to ICT is very pertinent to making women academics avail themselves of the benefits of ICT, but other factors that would make them become a part of the decision-making process regarding ICT issues should equally be addressed. The study recommends some policy options and strategies that the government and the management of the surveyed institutions should adopt. They should not only increase the access of women academics to ICT, but also enable them participate in the decision-making and control of ICT deployment.